Development of electrodeposited IrO2 electrodes as anodes in polymer electrolyte membrane water electrolysis - Lee, Byung-Seok; Ahn, Sang Hyun; Park, Hee-Young; Choi, Insoo; Yoo, Sung Jong; Kim, Hyoung-Juhn; Henkensmeier, Dirk; Kim, Jin Young; Park, Sehkyu; Nam, Suk Woo; Lee, Kwan-Young; Jang, Jong Hyun (Elsevier BV, 2015)
To reduce the use of noble metals, iridium oxide (IrO2) catalysts are prepared on carbon paper (CP) by electrodeposition for use as the anodes in polymer electrolyte membrane water electrolysis (PEMWE). The activities of the fabricated electrodes toward the oxygen evolution reaction are evaluated. The loading amount and morphology of the IrO2 deposits are varied by controlling the electrodeposition potential (E-dep) and time (t(dep)). When electrodeposited at 0.7 V. the IrO2 loading ranges from 0.007 to 0.464 mg cm(-2) (t(dep): 1 similar to 30 min). In the PEMWE test at 90 degrees C, the IrO2/CP electrode with an IrO2 loading of 0.1 mg cm(-2) shows the highest performance (1.92 A cm(-2) at 1.8 V) in which high IrO2 utilization is achieved without significant exposure of the substrate carbon surface. The developed IrO2/CP electrodes provide cell performances comparable to those in previous reports with a higher IrO2 loading, indicating markedly enhanced mass activity. (C) 2015 Elsevier B.V. All rights reserved.